The Edinburgh companion to Don DeLillo and the arts - Gander, Catherine (Edinburgh : Edinburgh University Press, 2023)
The first book to comprehensively address Don DeLillo's deep and lasting engagement with the arts across the entirety of his writing careerProvides the first comprehensive study of Don DeLillo's profound engagement with the visual, performing and plastic arts throughout his 50+ years career as a writerThe Edinburgh Companion to Don DeLillo and the Arts is the first book to provide a comprehensive study of Don DeLillo's career-long engagements with the visual, literary, digital and televisual, performing, filmic, and spatial arts. Gathering original essays from a diverse range of international contributors, including established voices in DeLillo criticism and emerging experts, the volume forges new paths in the study of one of the greatest authors of the twentieth and twenty-first centuries. Beginning with a section dedicated to experiential and political aesthetics in DeLillo's work, the Companion offers new perspectives on the forms and functions of the arts across DeLillo's entire oeuvre-from his first novel Americana, through his plays, essays, short stories, to his latest novel, The Silence. This exciting Companion is a genuine intervention in DeLillo scholarship by offering an interdisciplinary examination of his work across forms, media, method, and theory.
30. Going Up in the World: Architecture in the Works of Don DeLillo -- 31. 'Bird Lives': The High Art of Graffiti in Don DeLillo -- Notes on Contributors -- Index
Includes bibliographical references and index.
Description based upon online resource; title from PDF title page (DeGruyter, viewed October 16th, 2023).
In English.
eBooks on EBSCOhost
Keywords: DeLillo, Don -- Criticism and interpretation; DeLillo, Don; Theater -- Production and direction; Technology and the arts; Théâtre -- Production et mise en scène.; Technologie et arts; ART / American / General; Literature: history & criticism; Literary studies: fiction, novelists & prose writers; Modern & contemporary fiction; Fiction companions; Literature; Criticism, interpretation, etc